West Side story - Lehman, Ernest, 1915-2005.; Wise, Robert, 1914-2005.; Robbins, Jerome; Wood, Natalie; Beymer, Richard, 1939-; Tamblyn, Russ.; Moreno, Rita.; Chakiris, George; Bernstein, Leonard, 1918-1990.; Leven, Boris; Griffith, Robert E.; Prince, Harold, 1928-2019.; et al. (Santa Monica, Calif : MGM Home Entertainment, 2007)
This musical sets the tragedy of Romeo and Juliet against a backdrop of the rivalry of two street gangs, the Sharks and the Jets, in New York of the 1950s. A young woman who is sister to the Sharks leader has her first taste of love with the former head of the Jets.
CD: California dreamin' / The Mamas & the Papas -- It's my party / Lesley Gore -- Na na hey key kiss him goodbye / Steam -- Wild thing / The Troggs -- Baby love / Diana Ross & The Supremes -- I can't help myself (Sugar pie honey bunch) / Four Tops -- My girl / The Temptations -- Wooly booly / Sam the Sham & The Pharaohs.
Originally produced as a motion picture in 1961.
Based on the stage play produced by Robert E. Griffith and Harold S. Prince and the book by Arthur Laurents; play conceived, directed and choreographed by Jerome Robbins.
Compact disc contains music classics of the decade.
Accompanying booklet has title: Life: eye on the '60s.
Director of photography, Daniel L. Fapp ; editor, Thomas Stanford ; music, Leonard Bernstein ; costume designer, Irene Sharaff ; production designer, Boris Leven ; choreographer, Jerome Robbins.
Natalie Wood, Richard Beymer, Russ Tamblyn, Rita Moreno, George Chikiris.
Keywords: Gangs -- New York (State) -- Drama; First loves -- Drama; New York (State); Musical films; Film adaptations; Video recordings for the hearing impaired; Fiction films; Drama; Feature films